The analysis of cross‐correlation between Istanbul Stock Exchange and major stock markets and indices: An empirical analysis using Random Matrix Theory. (13th July 2022) - Taştan, Birhan; Imamoglu, Hatice
Abstract: This study attempts to investigate the cross‐correlation between stocks listed under the XU100 index of Borsa Istanbul with several ratios and indices of the stock markets worldwide by using the Random Matrix Theory approach through a correlation matrix. In addition, Eigenvector Analysis, Network Analysis, Dimension Reduction will be carried out to investigate cross‐correlation between markets. It was found that XU100, which is an index that includes 100 stocks highest in volume, has a distinguishing behavior compared to other indices and rates in terms of eigenvalue and related eigenvector structures. Furthermore, mean‐value portfolio analysis showed that the empirical correlation matrix underestimates the portfolio risks than the correlation matrix obtained by filtering the noise. Coronavirus pandemic also affected Borsa Istanbul by breaking periodic behavior of volatility and correlation cycle.